Reflections on Malaysian economic policies - Sulaiman Mahbob (Penerbit Universiti Malaya, 2015)
This book contains various articles written by Sulaiman Mahbob in the local media, especially in the New Straits Times and The Star. The topic covered are wide ranging, reflecting the concerns of the country particularly in the fields of development planning and national economic management.